2014
DOI: 10.1007/s11356-014-3281-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical stress and food limitation on the energy reserves and growth of turbot, Scophthalmus maximus

Abstract: The objective of the present study is to examine the growth and energetic performance of juvenile turbot after exposure to contaminated sediment and during the subsequent recovery period with or without food limitation. We designed a two-step experiment by first exposing juvenile turbot to harbour sediment for 26 days and then transferring them to clean sea water with different frequencies of feeding for 35 days. Without food limitation, fish previously exposed to contaminated sediment compensated for weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In past research on other organisms, the RNA/DNA ratio was measured as the RNA/DNA ratio variation in muscle tissue, but variations in liver tissue and the correlation of diurnal variations between hepatic and muscle tissues have seldom been reported (Kerambrun et al., 2014; Ji et al., 2016). Thus, some questions must be answered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In past research on other organisms, the RNA/DNA ratio was measured as the RNA/DNA ratio variation in muscle tissue, but variations in liver tissue and the correlation of diurnal variations between hepatic and muscle tissues have seldom been reported (Kerambrun et al., 2014; Ji et al., 2016). Thus, some questions must be answered.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the RNA/DNA ratio is related to not only the growth of aquatic animals (Tong et al., 2010) but also their nutrition status; consequently, the RNA/DNA ratio is a useful indicator of an organism's nutritional status. Recently, some studies have shown that the RNA/DNA ratio is a reliable and sensitive indicator of nutrient stress in organisms (Desai & Anil, 2002; Ji, Liu, Song, & Yang, 2016; Zehra & Khan, 2015), and the ratio has been applied to evaluate the nutritional status of organisms, including fish (Buckley, 1984; Kerambrun, Henry, Rabhi, & Amara, 2014; Liang, Wang, & Chen, 2001; Wang et al., 2008), crustaceans (Anger & Hirche, 1990) and aquatic reptiles (Ji, Xie, Liu, Li, & Yang, 2017; Ji et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological condition indices are useful tools to assess the effect of pollution on fish when variation in other environmental factors is limited. In a recent study, Kerambrun et al (2014) examined the growth and energetic performance of juvenile turbot after exposure to contaminated sediment and after a recovery period of 35 days in clean seawater with or without food limitation. In a recent study, Kerambrun et al (2014) examined the growth and energetic performance of juvenile turbot after exposure to contaminated sediment and after a recovery period of 35 days in clean seawater with or without food limitation.…”
Section: Recommendations and Limits Of Use Of Physiological Conditionmentioning
confidence: 99%